Utilization Of The Becak Tirtayasa Innovation In Reducing Leprosy Prevalence In The Tirtayasa Public Health Center Area, 2024 - Imaroh, Rifa; Angela Lumaksono, Maria; Hardiati, Rien; Imani, Izzah; Widasmara, Dhelya (Syntax Corporation, 2026)
Leprosy is a chronic infectious disease caused by Mycobacterium leprae that affects the peripheral nerves, skin, and other body tissues. In addition to medical consequences, leprosy poses complex social, economic, cultural, and public health challenges. The Tirtayasa Public Health Center oversees 14 villages with a total population of 50,937 people. As part of leprosy elimination efforts, the center developed the BECAK Tirtayasa Innovation, aimed at supporting the achievement of Triple Zero leprosy. This innovation includes the development of a leprosy counseling module, the formation of BECAK Tirtayasa cadres, establishment of a telemedicine group connecting cadres, leprosy officers, and doctors, implementation of health education and educational games on leprosy, active Intensified Case Finding (ICF), and provision of chemoprophylaxis. To analyze the utilization of the BECAK Tirtayasa Innovation in reducing leprosy prevalence in the Tirtayasa Public Health Center area in 2024. This study employed an observational analytical cross-sectional design involving 50 respondents selected through total sampling from leprosy cases recorded between 2019 and 2024. Most leprosy patients were adults aged 20–60 years (44 individuals; 88.1%) and male (27 individuals; 54%). The highest proportion of cases originated from Lontar Village (12 individuals; 24%). Multibacillary leprosy predominated (44 individuals; 88%), and the majority of patients presented with grade 1 disability (23 individuals; 46%). The highest number of leprosy cases was recorded in 2019 (17 cases), while the lowest occurred in 2024, with only one new case identified. In 2024, the implementation of the BECAK Tirtayasa Innovation was associated with a decrease in leprosy prevalence to 0.1 per 10,000 population and achievement of the new case detection target at 1.9 per 100,000 population. No grade 2 disability cases or pediatric leprosy cases were reported (0%), and the treatment completion rate exceeded the national target (100%). Leprosy cases in the Tirtayasa Public Health Center area predominantly affected adult males, were mostly multibacillary in type, and commonly presented with grade 1 disability. The BECAK Tirtayasa Innovation contributed to a reduction in leprosy prevalence and supported progress toward Triple Zero leprosy in the Tirtayasa Public Health Center area.